Mobile Augmented Reality (AR) Learning Media on Distance Material in Three Dimensions - Andika Saputra; Nurul Iman (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
The purpose of this research is to develop a mobile learning media based on augmented reality (AR) that can be used and can improve student achievement in learning mathematics on distance material in three dimensions. The approach method used in this research is R&D (Research and Development). In media development, the steps taken are as follows; research, data collection, planning, product draft development, product validation, revision of product validation results, field trials, revision of field trial results, final product improvement, and dissemination. Meanwhile, in assessing the success of the media in improving student learning achievement, the Paired Sample T-test statistical method was used. The results obtained in this study are that a mobile learning media augmented reality (AR) has been successfully developed on distance material in three dimensions in the form of an android application, which can be used and proven to significantly improve student achievement in mathematics learning on distance material in three dimensions